Analysis of Leadership Style and Organizational Culture on the Performance of Employees of the Directorate of Commercial Order of the Ministry of Trade with Organizational Commitment as a Mediation Variable - Geiger Fransisco Nainggolan; M. Chaerul Rizky; Kholilul Kholik (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of leadership style and organizational culture on employee performance with organizational commitment as a mediating variable at the Directorate of Commercial Order of the Ministry of Trade. This study uses a quantitative method with a causal associative approach. The research population was all employees of the Directorate of Trade Order of the Ministry of Trade totaling 141 people, with a sample of 59 respondents determined using the Slovin formula and simple random sampling techniques. Data was collected through a structured questionnaire distributed through Google Form and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS software. The results of the study show that: (1) Organizational Culture has a positive and significant effect on Organizational Commitment; (2) Organizational Culture does not have a significant effect on Employee Performance; (3) Leadership Style does not have a significant effect on Organizational Commitment; (4) Leadership Style has a positive and significant effect on Employee Performance; (5) Organizational Commitment has a positive and significant effect on Employee Performance; (6) Organizational Commitment is able to mediate the influence of Organizational Culture on Employee Performance; and (7) Organizational Commitment is not able to mediate the influence of Leadership Style on Employee Performance. This study concludes that organizational commitment is a dominant factor that affects employee performance and plays a mediator in the relationship between organizational culture and employee performance.